Barreiras e facilitadores para a adoção das práticas de economia circular em negócios empreendedores sustentáveis no setor de energia solar fotovoltaica do Brasil - Teixeira, Marco Antonio Casadei (2024)
The transition to sustainable entrepreneurship promotes both awareness and resilience while contributing to the preservation of natural resources and the building of a more balanced future. In this context, Circular Economy (CE) emerges as an innovative approach to sustainable development, offering a robust alternative to the traditional linear economic model. CE not only promotes environmental conservation but also drives innovation and creates new economic and employment opportunities. This approach stimulates a shift towards a more resilient and sustainable economy, addressing growing concerns about environmental degradation. Sustainable business models leverage CE principles to develop strategies aimed at reducing resource waste, increasing reuse, and decreasing environmental impact. The use of photovoltaic solar energy harnesses sunlight, an abundant and renewable energy source, to generate electricity cleanly and efficiently. In addition to reducing dependence on fossil fuels, photovoltaic solar energy minimizes greenhouse gas emissions, contributing to climate change mitigation. Thus, incorporating photovoltaic solar energy into business models not only promotes environmental sustainability but also encourages technological innovation and economic development, aligning with fundamental CE principles. Developing sustainable entrepreneurial businesses requires an understanding of barriers and facilitators. It is essential for entrepreneurs to grasp elements that can hinder or drive business progress, empowering them to make well-informed decisions and identify areas for continuous improvement. The central question of this research was: "What are the barriers and facilitators to adopting CE practices in sustainable entrepreneurial business models in the photovoltaic solar energy sector in Brazil?" Therefore, the general objective of the study was to analyze the barriers and facilitators to adopting CE practices in sustainable entrepreneurial business models in Brazil's photovoltaic solar energy sector. This thesis comprises three interconnected and sequential studies. The first study conducted a systematic literature review to explore the intersection between Circular Economy (CE) and Entrepreneurship. It reviewed 84 publications up to 2022, identifying seven key themes: Industrial Symbiosis, Supply Chain, Product Life Cycle, Circular Business Models, Sharing Platforms, Producer-Consumer, and Product-Service Systems. This study underscored the importance of integrating CE and Entrepreneurship, highlighting opportunities for innovation and sustainable growth, such as energy transformation, value creation, and waste management. In the second study, the research investigated the relationship between Circular Economy (CE) and sustainable entrepreneurship, focusing on the adoption of circular practices by entrepreneurial businesses. The systematic literature review involved 48 studies, revealing that most research employs empirical qualitative methods to explore practical aspects and real experiences of sustainable enterprises. Results highlighted both internal and external barriers and facilitators influencing the adoption of these practices. The third qualitative study explored the barriers and facilitators to adopting Circular Economy (CE) practices in sustainable entrepreneurial businesses, specifically in the photovoltaic solar energy sector. Several barriers were identified, such as high initial costs, regulatory complexity, and cultural resistance to change, contrasted with facilitators such as government financial incentives, technological advancements, and increasing environmental awareness. This study has significant social impact by promoting the transition to more sustainable and circular business models, aiming not only to reduce environmental impact but also to improve the quality of life in communities around these operations. This occurs through the creation of green jobs and the promotion of business practices that respect ecological limits. Furthermore, by identifying barriers and facilitators to CE adoption, the study can inform public policies and governmental strategies that encourage sustainable practices. This may result in financial and regulatory support initiatives favoring the development of sustainable businesses, thereby increasing the involvement of small and medium enterprises in the renewable energy market.